Paradigma Baru Konsepsi Wasiat Wajibah Bagi Ahli Waris yang Terhalang Memperoleh Bagian Harta Warisan - Fitri, Al (Legalita, 2024)
Abstract Wasîat wajîbah is a study of contemporary Islamic family law, which emerged as an answer to the problem of inheritance in diverse Indonesian society due to the existence of heirs (relatives) who do not receive tirkâh from the deceased because of the sharia prohibition on accepting it. inheritance, for example, inheritance for adopted children, and stepchildren, grandchildren of daughters and husband and wife who have different religions or are apostates. Conditions like this cannot be separated from the reality of social conditions in society, including norms, structures, and traditions passed down from generation to generation that have existed for a long time (living law). The granting of inheritance rights to them through the wajîbah will institution merely accommodates local wisdom to maintain justice for Muslims in Indonesia. This research examines the main problem, namely whether the legal instrument of granting inheritance rights using a mandatory will is an appropriate alternative. This research uses a method called analytical descriptive. From this research, results were obtained which show that the use of the wajîbah will institution to resolve new cases in inheritance law has a juridical reason by using the concept of justice to guarantee legal certainty for adopted children, stepchildren, grandchildren of daughters and husband and wife, of different religions because inheritance is prohibited. Keywords: mandatory will, justice, tirrkah